2012
DOI: 10.4097/kjae.2012.62.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal rupture after endotracheal intubation - A report of three cases -

Abstract: Tracheal rupture is a rare but serious complication that occurs after endotracheal intubation. It usually presents as a linear lesion in the membranous wall of the trachea, and is more prevalent in women and patients older than 50 years. The clinical manifestations of tracheal injury include subcutaneous emphysema and respiratory distress. We report the cases of three female patients of old age presenting tracheal rupture after endotracheal intubation. Two cases received surgical repair without complication an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
3

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 15 publications
0
52
0
3
Order By: Relevance
“…ETT cuff pressure below 20 cmH 2 O is a risk factor of ventilator associated pneumonia [ 1 , 2 ]. However, over-inflation of the ETT cuff can cause a serious injury and affect blood flow to the tracheal mucosa [ 3 ], resulting in tracheal stenosis, tracheoesophageal fistula, or tracheal rupture [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…ETT cuff pressure below 20 cmH 2 O is a risk factor of ventilator associated pneumonia [ 1 , 2 ]. However, over-inflation of the ETT cuff can cause a serious injury and affect blood flow to the tracheal mucosa [ 3 ], resulting in tracheal stenosis, tracheoesophageal fistula, or tracheal rupture [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In ation of the endotracheal tube cuff to the correct pressure is one of the elements in properly conducted intubation. Carrying out the procedure correctly is di cult when it is done using a syringe [2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Research in other countries has shown that assessment of cuff in ation using the palpation technique is relatively ineffective and rarely results in correct cuff in ation. Experienced paramedic specialists using the palpation technique to assess the amount of air in the cuff during intensive care conduct the procedure correctly in less than 30% of cases [2][3][4][5]. It has been proven that during palpation assessment, the cuff seal is overin ated, even to as high as 100 cm H2O [4].…”
Section: Introductionmentioning
confidence: 99%
“…Dans la majorité des sé ries publié es, le sexe fé minin, la taille infé rieure à 160 cm et l'âge supé rieur à 50 ans apparaissent comme é tant des facteurs favorisant de rupture traché ale post-intubation [4][5][6][7]. La fragilité de la pars membranosa traché ale dans cette population pourrait en être le support anatomique [8].…”
Section: Discussionunclassified